The Role of Neuroglia in the Development and Progression of Schizophrenia - Neha S. Rawani; Allen W. Chan; Kathryn G. Todd; Glen B. Baker; Serdar M. Dursun (Biomolecules)
Schizophrenia is a complex heterogenous disorder thought to be caused by interactions between genetic and environmental factors. The theories developed to explain the etiology of schizophrenia have focused largely on the dysfunction of neurotransmitters such as dopamine, serotonin and glutamate with their receptors, although research in the past several decades has indicated strongly that other factors are also involved and that the role of neuroglial cells in psychotic disorders including schizophrenia should be given more attention. Although glia were originally thought to be present in the brain only to support neurons in a physical, metabolic and nutritional capacity, it has become apparent that these cells have a variety of important physiological roles and that abnormalities in their function may make significant contributions to the symptoms of schizophrenia. In the present paper, we review the interactions of brain microglia, astrocytes and oligodendroglia with aspects such as transmitter dysregulation, neuro-inflammation, oxidative stress, synaptic function, the gut microbiome, myelination and the blood–brain barrier that appear to affect the cause, development and treatment of schizophrenia. We also review crosstalk between microglia, astrocytes and oligodendrocytes and the effects of antipsychotics on neuroglia. Problems associated with studies on specific biomarkers for glia in schizophrenia are discussed.